Characterization of m-GaN and a-GaN Crystallographic Planes after Being Chemically Etched in TMAH Solution - Nedal Al Taradeh; Eric Frayssinet; Christophe Rodriguez; Frederic Morancho; Camille Sonneville; Luong-Viet Phung; Ali Soltani; Florian Tendille; Yvon Cordier; Hassan Maher (Energies, 2021)
This paper proposes a new technique to engineer the Fin channel in vertical GaN FinFET toward a straight and smooth channel sidewall. Consequently, the GaN wet etching in the TMAH solution is detailed; we found that the m-GaN plane has lower surface roughness than crystallographic planes with other orientations, including the a-GaN plane. The grooves and slope (Cuboids) at the channel base are also investigated. The agitation does not assist in Cuboid removal or crystallographic planes etching rate enhancement. Finally, the impact of UV light on m and a-GaN crystal plane etching rates in TMAH has been studied with and without UV light. Accordingly, it is found that the m-GaN plane etching rate is enhanced from 0.69 to 1.09 nm/min with UV light; in the case of a-GaN plane etching, UV light enhances the etching rate from 2.94 to 4.69 nm/min.